Understanding ICT Adoption Determinants among Indonesian SMEs in Fashion Subsector - Setiowati, Rini; Hartoyo, Hartoyo; Daryanto, Heny K.; Arifin, Bustanil (International Research Journal of Business Studies, 2015)
This paper investigates factors that affect the adoption of Information Communication and Technology (ICT) among SMEs in fashion subsector in Indonesia. This study adopts Technology, Organization, and Environment (TOE) framework which consist technological factors such as relative advantage, compatibility, complexity, trialability, observability; organizational factors such as owner/manager IT knowledge, owner/manager innovativeness;and environmental factors namely competitive pressure, market turbulence, and institutional intervention. A questionnaire-based survey was used to collect data from 204 SME owners/managers. The results show that under technological factors, compatibility, complexity, trialability, and observability significantly and positively influence ICT adoption. However, relative advantage and complexity have significant but negative influence on ICT adoption. Moreover, the organizational factors namely owner/manager’s knowledge and innovativeness also contribute significantly to the adoption. Furthermore, among three environmental factors, competitive pressure and institutional intervention are determinants that influence ICT adoption in SMEs, whereas market turbulence shows no significant contribution toward the adoption of ICT. This study provides valuable insights for government and policy makers as well as for SMEs owner/managers to develop strategies that promote and foster the adoption of ICT.